Effect of an endocrine disruptor on mammalian fertility. Application of monoclonal antibodies against sperm proteins as markers for testing sperm damage - Peknicová, Jana; Kyselová, Vendula; Buckiová, Dana; Boubelík, Michael (American journal of reproductive immunology (New York, N.Y., 2002)
PROBLEM: To determine the influence of an endocrine disruptor [bisphenol-A (BPA)] on the integrated reproductive process as well as on individual reproductive organs and gametes in order to select suitable markers for testing sperm damage. METHOD OF STUDY: The effect of BPA on fertility in vivo in multigenerational studies in an outbred stock of mice was studied. Damage of reproductive organs was assessed by histochemical methods and damage of spermatozoa by means of a panel of monoclonal antibodies (MoAbs) against intra-acrosomal sperm proteins. RESULTS: BPA had a negative influence on offspring born of mice, on reproductive organs, and on acrosome integrity of mice spermatozoa. Selected MoAbs against intra-acrosomal mammalian sperm proteins, cross-reacted with mouse spermatozoa, were used for determination of the acrosome integrity. BPA had no effect on body weight and testicle weight of males. CONCLUSIONS: The present results demonstrate that BPA has a negative effect on in vivo fertility of mice, with impact on spermatogenesis and sperm quality. Monoclonal antibodies against intra-acrosomal sperm proteins can be used for detecting sperm damage.
Keywords: Cross Reactions; Fertility; Male; monoklonální protilátky; biologické markery; akrozom; zkřížené reakce; Estrogens, Non-Steroidal; Biomarkers; spermatogeneze; Pregnancy; těhotenství; Spermatozoa; Spermatogenesis; mužské pohlaví; fenoly; benzhydrylové sloučeniny; Acrosome; fertilita; Animals; nesteroidní estrogeny; ženské pohlaví; zvířata; spermie; myši; Antibodies, Monoclonal; Benzhydryl Compounds; Phenols; Mice; Female